Mean-State Arctic Sea Ice Transitions During 1979–2024 and the Underlying Physical Processes - Xia Lin; Yingrui Zhu; Weijia Li; Meibing Jin; Jingyi Huang; Xiuhao Guo; Xiaochun Wang; Jianfen Wei; Zhitong Lai; Changming Dong (Journal of Marine Science and Engineering, 2025)
Amplified Arctic warming has led to a pervasive decline in sea ice cover over recent decades; yet, the pattern and governing mechanisms of sea ice concentration (SIC) state transitions remain unclear. This study reveals pronounced regional contrasts in mean-state SIC during the transition from 1979–2006 to 2007–2024, concurrent with a reduction in the sea ice extent over the same period. The September-mean sea ice in the 70° N–80° N Arctic belt retreated significantly from 1979–2006 to 2007–2024, while the Barents and Greenland Seas exhibited persistent ice loss in March. Enhanced ice-albedo feedback, together with concurrent rises in the 2 m air temperature and sea surface temperature, dominate these ice loss processes. Dynamical processes exert distinct regulatory roles in September and March. The strengthened Beaufort High induces sea ice convergence to partially offset the September thermodynamically driven ice loss, while the positive-phase Arctic Dipole in March amplifies the transpolar airflow and winds over the Greenland and Barents Seas and triggers rapid sea ice export and significant loss in these regions. These findings underscore the spatial heterogeneity of Arctic SIC transitions and highlight the complex interplay of thermodynamic and dynamic processes shaping them.